Weight Pressures and Eating Disorder Symptoms among Adolescent Female Gymnasts of Different Performance Levels in Greece - Ioanna Kontele; Tonia Vassilakou; Olyvia Donti (MDPI AG, 2022)
This study examined the weight pressures within the gymnastics environment and explored associations between these pressures and eating disorder (ED) symptoms in adolescent female gymnasts. One hundred and forty-seven competitive gymnasts and 122 recreational-level gymnasts (11-17 years old) completed the Eating Attitudes Test (EAT-26), the Weight-Pressures in Sport-Females (WPS-F), the Social Desirability Scale (SDS) and provided information on their training. It was found that 16.3% of competitive gymnasts and 7.4% of non-competitive gymnasts scored ≥20 in EAT-26, indicating disordered eating behavior. Competitive gymnasts scored higher than non-competitive in the total score of EAT-26 (p = 0.027), as well as in the total score of WPS-F, the sport and coaches weight pressures sub-scale and the appearance and performance weight pressures sub-scale (p < 0.001). Multiple regression analyses indicated that sport and coaches weight pressures, appearance and performance weight pressures and body mass index accounted for 30.3% of the variance of EAT-26 in competitive gymnasts, while the appearance and performance weight pressures sub-scale accounted for 16.3% of the variance of EAT-26 in non-competitive gymnasts. Sport and coaches weight pressures are associated with ED in competitive gymnasts, while body appearance and performance demands correlate with ED in female gymnasts irrespective of competitive level.